Liking and Disliking Factors about going to School perceived by the Parents of Children with Special needs enrolled in Special Schools of Lahore City - Fazil, Hina; Zulfiqar, Attia; Nawaz, Hifza (Annals of Human and Social Sciences, 2023)
Online business has been turned into an effective opportunity for students, especially at This paper aimed to investigate the liking and disliking factors of school-going children with special perceived by their parents and to compare the liking and disliking of school-going special needs children. The quantitative research approach was applied by the researchers to complete the study. 40 parents of school-going children with special needs residents of Lahore city were selected as a sample by using a stratified sampling technique for this research. One close-ended self-constructed reliable questionnaire (Cronbach Alpha=.84) was used by the researchers (Cronbach Alpha=.84). The results pinpointed liking to do activities in the school more than disliking (liking score= 83.7500 and disliking score=52.5500). There is no significant difference in parental views based on their gender about the total liking (t=.388, df=38 and p=.700) and disliking factors (t=.788, df=38, and p=.436) and there are no significant differences in the liking and disliking of students with special needs based on their disabilities about going to school. Researchers recommended that reinforcement should be given to the special needs students to maintain their likeness for attending school.